Characterizing the variability and meteorological drivers of wind power and solar power generation over Africa. (10th October 2022) - Bloomfield, Hannah C.; Wainwright, Caroline M.; Mitchell, Nick
Abstract: Sub‐Saharan Africa (SSA) has the lowest energy access rates in the world, which poses a key barrier to power system development. Deployment of renewables, including wind and solar power, will play a key role in expanding electricity supply across SSA: distributed generation (enabling access for remote communities), cost‐effectiveness and low emissions are key advantages. However, renewable generation is weather dependent; therefore, including more renewables increases the amount of meteorologically driven variability in the power system. Two countries in SSA are chosen for detailed investigation of this meteorologically driven variability: Senegal in West Africa and Kenya in East Africa. These are chosen due to being areas of dense population, where there is operational wind and solar power, and plans for regional expansion. In Senegal, solar generation is fairly consistent throughout the year, while wind generation exhibits strong seasonality, with a peak in the boreal spring. Low wind and solar power generation days during the boreal summer are found to be related to the passage of African Easterly Waves. Over Kenya, both wind and solar generation exhibit seasonal variability, with wind generation peaking during boreal autumn, and solar generation at a minimum during boreal summer. Inter‐annual variability in generation is greater over Kenya than over Senegal; the El Nino Southern Oscillation is found to impact wind and solar generation over Kenya. El Nino phases are associated with lower wind and solar generation in October–December over Kenya, but higher generation in July–September. This improved understanding of variability will assist system planners in designing reliable future energy systems. Abstract : Deployment of renewables in sub‐Saharan Africa, including wind and solar power, will play a key role in expanding electricity supply and furthering energy access. However, including more renewables increases the amount of meteorologically driven variability in the power system. Senegal and Kenya are chosen for a detailed investigation of this meteorologically driven variability. The complementarity of existing wind and solar generation is explored, as well as the dependence on African Easterly Waves, the Turkana Jet and the El Nino Southern Oscillation.